Contribution to the Study of the European Ground Squirrel’s Population (Spermophilus citellus Linnaeus, 1766) in Rila National Park, Bulgaria - Emanuil Mitrevichin; Lidia Sakelarieva (Studia Ecologiae et Bioethicae)
Although there are still some large and stable populations of the European Ground Squirrel, there has been a serious decline in the number and density of most of the species populations throughout its range, including in Bulgaria. The aim of the study is to supplement the scientific data about the population of the European Ground Squirrel and its habitat in Rila National Park, Southwestern Bulgaria. The research was carried out in 2017-2019 in two study areas, each divided into 20 (21) transects (every 100 m long and 5 m wide). The results have shown that the relative population density based on the number of holes tends to decrease in the period of study. The most likely reason for this, and the most significant identified threat to the population of the species in the research area in general, is the observed deterioration of the habitat status.